(untitled) (Sociologisk Forskning, 1998)
Media power and media criticism: Towards a mapping of the field of media criticism In the late 90s critical debate and research on the media have gained wide attention. Media criticism and critique is becoming a central political, social and scientific issue. In the article the concept of media criticism is discussed. Media criticism is interpreted as public discourse assessing the media and media impact. Beyond a dialogue on media policy and media practice, criticism offers highly polarized and partly mystifying accounts of the media and its social and cultural impact. The heated debate on media is interpreted as part of a social struggle between different social institutions (markets, politics, science and media) and as different models for action and knowledge. New forms and arenas for media criticism are also suggested and discussed.